Republic of Kosovo Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
Kosovo is Europe’s youngest country in terms of history and demographics. Both characteristics are defining the country’s overarching development challenges. The country’s geographical position along major trade routes made its territory a pawn in the hands of powerful neighbors, from the Romans and the Ottoman Empire to Yugoslavia. The considerable amount of self-governance granted to Kosovo under the Yugoslav Constitution of 1974, as a province of Serbia, but not as a constituent republic of the federation, proved politically unsustainable, as temporary gains in self-rule were reversed by Belgrade during the Milosevic era. The period after 1989 was characterized by increased repression and violence, culminating in war and population expulsion in 1998–99. During the immediate post conflict period, United Nations (UN) Security Council Resolution 1244 placed Kosovo under UN interim administration. In 2008, Kosovo declared independence. The transition period of supervised independence ended four and a half years later. International recognition has remained partial and has precluded Kosovo from joining the UN as a full member.4 In the wake of these developments, public institutions had to be established from scratch and earn the population’s acceptance and credibility as their own. The remainder of this document is organized as follows. Section two presents the country context, including political and economic conditions, and discusses factors behind recent trends in growth, shared prosperity, and poverty. It concludes with a proposed conceptual framework. Sections three–six describe key drivers and the principal constraints to growth, shared prosperity, and poverty reduction. Section seven examines the priority areas for action.